Trends in practice and outcomes from 2011 to 2015 for surgical aortic valve replacement: an update from the German Aortic Valve Registry on 42 776 patients - Fujita, Buntaro; Bekeredjian, Raffi; Katus, Hugo (European journal of cardio-thoracic surgery, 2018)
AbstractOBJECTIVES:. Surgical aortic valve replacement (sAVR) is coming under close scrutiny with the recent upswing in the use of less invasive approaches. Th